Perceived Social Acceptability of Deception as a Function of Culture, Motive and Relationship: A Cross-Cultural Study of Majority Speech Communities in Finland, China and the United States - Parrott, Kari J. (My University, 2012)
This study explores the influence of culture on how deception is perceived as a sociably acceptable form of communication within different speech communities. The study extends to Finland a previous study conducted via a questionnaire in the United States and China that explored how the cultural background of the participant, the motive for lying, and the type of relationship between the speaker and receiver presented through several scenarios affected perceived acceptability. It is hypothesized that individualistic cultures will evaluate deception similarly, and therefore Finnish participants will evaluate the scenarios in a manner that is more consistent with the US participants than the Chinese participants. It is also hypothesized that Finnish participants will perceive an overall lower social acceptability for deception across the board. Hofstede’s Individualism/Collectivism dimension is used as a theoretical basis for categorizing the majority speech communities in Finland, China and the US as individualistic or collectivistic. The study pursues a mainly quantitative approach using a questionnaire to collect numerical assessments of perceived acceptability of various scenarios in which a lie is told. A limited qualitative approach is also taken through an analysis of two open-ended questions included in the questionnaire. The results indicate that Hofstede’s Individualism/Collectivism dimension does not provide an adequate predictive model for questions regarding social acceptability of deception. Depending on whether the motive is considered positive or negative, the Finnish group rated the scenario more similarly to the Chinese group or more similarly to the US group, respectively, showing slightly more consideration for motive than the other two groups. On average overall, the Finnish group’s ratings are midway between the ratings of the other two groups. The results, their implications, and possibilities for future research are discussed.
Keywords: Deception; Cross-cultural communication; Finland; United States; China; Social acceptability; fi=Viestintätieteet|en=Communication Studies|; fi=Master's Degree Programme in Intercultural Studies in Communication and Administration|